IoT-Based Smart Metering for Electricity and Water Monitoring and Billing in Boarding Houses - Prasojo, Kholik; Ashari, Hilda (Jurnal Media Elektrik, 2026)
This study aimed to develop and evaluate an Internet of Things (IoT)-based smart boarding house meter for monitoring and recording electricity and water consumption to support accurate billing. The system integrates hardware components (sensors and microcontroller) with an Android-based application to enable real-time monitoring and automated cost calculation. This research employed the research and development (R&D) method using a prototyping model consisting of requirements analysis, prototype development, system coding, and testing. System evaluation included hardware functionality testing using black-box testing, application testing using structured test cases, and effectiveness testing by comparing sensor readings with standard measurement instruments. Data were analyzed using a descriptive quantitative approach based on percentage calculations. The results showed that both the hardware and application functions achieved a 100% success rate according to the functional testing criteria. The effectiveness test indicated an average sensor accuracy of 95%, demonstrating reliable system performance. The novelty of this study lies in the integration of electricity and water monitoring into a single IoT-based system with automated billing and remote control features. The developed system is feasible for implementation and can improve efficiency, transparency, and accuracy in boarding house utility management.